Efek Waktu Pasar dan Kebijakan Investasi terhadap Struktur Modal - Pontoh, Winston (Universitas Sam Ratulangi, 2014)
The capital structure policy by an entity is still a question specially in the context of investment policy and if related to market timing. The question is still exist because the entity faced by two options of financing which are internal financing (capital) and external financing (debt). This study is using data from the samples of 241 entities listed in Indonesia Stock Exchange in period of 2009 till 2012 making the total of observed data are 964. Conducting multiple regression analysis, this study conclude that, the effect of pecking order, trade off and market timing are not absolute for all conditions of entities, because the entities will take decision for capital structure policy based on its conditions such as internally or externally. In this case, the external condition is referring to capital market.